Adaptation and Transformation of Pesantren Education in Facing The Era of Muslim Society 5.0 - Mutammam; Dewi Anggraeni; Akhmad Afroni; Sutrisno; Aisyah Zubaidah; Gumilar Irfanullah (Universitas Pesantren Kh abdul Chalim Mojokerto, 2024)
This study aims to analyze the transformation of education in Pesantren Al Hikmah 02 Benda in facing the era of Society 5.0. The research method used is qualitative with a case study approach. Data were collected through interviews with caregivers, teachers, administrators, and Santri, as well as through participant observation and documentation. Qualitative research analysis was strengthened by SWOT analysis to identify the potential of pesantren in facing new challenges in the era of Society 5.0. The results showed: a) The transformation of Pesantren Al Hikmah 02 refers to the principle of Al-muhafadzatu 'ala alqadimi alshalihi wa al akhdu bi al jadidi al ashlah; b) Transformation in the 4.0 era has an impact on the resilience and sustainability of the pesantren education system, by referring to the AGIL system (Adaptation, Goal Attainment, Integration, Latency); c) The Three in One innovative curriculum is used as a strategy to answer the challenges of the era of Muslim Society 5.0. The Three in One curriculum innovation strategy can be a model for other Pesantren in facing the challenges of the digital era and industrial revolution. The transformation of Pesantren education while maintaining the values and traditions of Pesantren can contribute to the development of adaptive and sustainable Pesantren education.